VISUALISASI MOTIF BATIK SUMATERA PADA HIASAN DINDING - Yuni Yumarni; Eliya Pebriyeni (Institut Seni Indonesia Padangpanjang, 2022)
Sumatra batik is batik originating from the island of Sumatra. The variety and motifs of Sumatran batik cannot be separated from the elements related to each region of origin. From this, not everyone understands the form, meaning, and meaning behind batik motifs in Sumatra. The object that the author makes in the work is the form of traditional houses in each region in Sumatra. This work is made in the form of traditional houses in each area and applies or places motifs that are appropriate for each region. This work introduces the forms of motifs in Sumatra and also the forms of traditional houses in Sumatra. Helping the community in reintroducing the forms of batik motifs in Sumatra. From these motifs to make Sumatran batik motifs as an idea in creating a work of art in the form of wall decoration. Ten works with the title Aceh, North Sumatra, West Sumatra, South Sumatra, Riau, Riau Islands, Lampung, Jambi, Bengkulu and Bangka Belitung Islands.